2013
DOI: 10.2139/ssrn.2298271
|View full text |Cite
|
Sign up to set email alerts
|

Logistic Regression for Extremely Rare Events: The Case of School Shootings

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…These factors were optimally clustered with anxiety and depression. The results obtained in this study are validated by other studies that have indicated that patients with anxiety and osteoporosis easily encounter more complications than those with several other disease groups [ 29 , 30 , 31 ]. The results of this study indicate that young patients with lung cancer and osteoporosis are also at a high risk for the onset of anxiety.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These factors were optimally clustered with anxiety and depression. The results obtained in this study are validated by other studies that have indicated that patients with anxiety and osteoporosis easily encounter more complications than those with several other disease groups [ 29 , 30 , 31 ]. The results of this study indicate that young patients with lung cancer and osteoporosis are also at a high risk for the onset of anxiety.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, young female lung cancer patients were also at a higher risk of the onset of depression. Previously published studies have shown that female cancer patients are at significantly higher risk of depression than males [ 29 , 32 , 33 ]. In this study, the clustering results also supported that young female lung cancer patients were at a higher risk of the onset of depression.…”
Section: Discussionmentioning
confidence: 99%
“…I use Firth’s penalized maximum likelihood estimation as well as the bias correction method (rare events logit) to conduct robustness checks (King & Zeng, 2001), because the dependent variable involves rare events and low-frequency data. I also include a non-penalized logit model, because some argue that logistic regression models are suitable even for extremely rare events (Westphal, 2013).…”
Section: Methodsmentioning
confidence: 99%